KEGIATAN KEAGAMAAN DALAM MENINGKATKAN PERILAKU SOSIAL SISWA KELAS IX SMP WAHID HASYIM MALANG - Masning Murthosyiyah; Mutiara Sari Dewi; Atika Zuhrotus Sufiyana (Vicratina : Jurnal Ilmiah Keagamaan, 2022)
Religious activities in the school environment are realized to create student who can serve Allah SWT and love others. This aims to fortify students from outside cultural influences that are not in accordance with the norms in Islamic teachings. Activities that are well conseptualized and can be carried out consistently will provide the best results for students. The method used in this research is qualitative research with the type of case study research. Data collection techniques using the method of observation, interviews and documentation. Data analysis techniques used are data reduction, data display and conclusions. Checking the validity of the data using a credibility test which consists of extending observations, increasing persistence and triangulation. The results of the study found that religious activities in the school environment can improve student behavior and mutual cooperation. This is obtained because of good planning, consistency, emphasis, motivation and example in its implementation